Cardiovascular outcomes of cancer patients in rural Australia - Williams, Trent D.; Kaur, Amandeep; Warner, Thomas; Aslam, Maria; Clark, Vanessa; Walker, Rhonda; Ngo, Doan T. M.; Sverdlov, Aaron L. (Frontiers in Cardiovascular Medicine, 2023)
Background Cancer and heart disease are the two most common health conditions in the world, associated with high morbidity and mortality, with even worse outcomes in regional areas. Cardiovascular disease is the leading cause of death in cancer survivors. We aimed to evaluate the cardiovascular outcomes of patients receiving cancer treatment (CT) in a regional hospital. Methods This was an observational retrospective cohort study in a single rural hospital over a ten-year period (17th February 2010 to 19th March 2019). Outcomes of all patients receiving CT during this period were compared to those who were admitted to the hospital without a cancer diagnosis. Results 268 patients received CT during the study period. High rates of cardiovascular risk factors: hypertension (52.2%), smoking (54.9%), and dyslipidaemia (38.4%) were observed in the CT group. Patients who had CT were more likely to be readmitted with ACS (5.9% vs. 2.8% p = 0.005) and AF (8.2% vs. 4.5% p = 0.006) when compared to the general admission cohort. There was a statistically significant difference observed for all cause cardiac readmission, with a higher rate observed in the CT group (17.1% vs. 13.2% p = 0.042). Patients undergoing CT had a higher rate of mortality (49.5% vs. 10.2%, p ≤ 0.001) and shorter time (days) from first admission to death (401.06 vs. 994.91, p ≤ 0.001) when compared to the general admission cohort, acknowledging this reduction in survival may be driven at least in part by the cancer itself. Conclusion There is an increased incidence of adverse cardiovascular outcomes, including higher readmission rate, higher mortality rate and shorter survival in people undergoing cancer treatment in rural environments. Rural cancer patients demonstrated a high burden of cardiovascular risk factors.